Sound, voice, music: Editorial - Danijela Kulezic-Wilson; Christopher Morris; Jessica Shine (Alphaville: Journal of Film and Screen Media, 2012)
Not so long ago, film music scholars complained habitually that, despite its established and powerful role in the media economy of film, music was being neglected by film and music studies alike. The multidisciplinary nature of film music studies was often cited as a possible reason for this state of affairs: film scholars felt they lacked sufficient musical education, or simply the terminology, to address the matter, while musicologists sniffed at what seemed to them a demeaning appropriation of music in the service of mere illustration or mood-setting. The division between film theory and film music theory was further exacerbated by the perception cultivated by some film scholars that music represented an addition to, rather than an integral part of, film (Kalinak). Not that the early literature on film music did much to suggest otherwise: largely anecdotal in nature, it documented the use of music in silent and early sound films in ways that seemed to reinforce the notion of music as post-production in practice and an after-thought to theory.